L’etica fenomenologica di Edith Stein - Wulf, Mariéle (B@belonline, 2021)
The text, based on Nicoletta Ghigi's book, Edith Stein's Phenomenological Ethics, examines the concept of responsibility, which includes an analysis of the structure of the person and an analysis of motivation. In particular, it outlines the formation of responsibility and offers a source to stimulate good decision-making: God's grace, especially visible in the causality of the inner encounter with God. It develops the notion of "formation" (Bildung) and an ethics of formation. Important is the analysis of the motivational structure, of the soul developed in Stein's anthropology, which arrives at a final dimension: The nucleus is the source that lies in the depths of the soul. Growing towards the deepest part of the self is the greatest ethical challenge and finally the most fruitful.